Faktor-Faktor Yang Mempengaruhi Nilai Aktiva Bersih Reksadana Manulife Syariah Sektor Amanah - Yesika Novita Lintang Gumilang; Leo Herlambang (Universitas Airlangga, 2017)
Mutual funds can be bridging For Small investors but Want to invest hearts Capital Markets Namely mutual funds, but so far there is hardly any who see mutual funds as part of an attractive investment exceeds savings, deposits, or even stocks.There is factors that affect Net Asset Value namely interest rates and market unsystematic risk. Based on this study proved this study uses a quantitative approach to the study results The results of this study is the Effect of interest rate and market unsystematic risk to Net Asset Value simultaneously significantly.The influence of interest rates on the second partial Net Asset Value significantly, interest rates affect the Net Asset Value of 99.4%, which means have a strong influence on the NAB. The effect of market unsystematic risk on a third partially NAB insignificant. market unsystematic risk affect the NAB amounted to only 66.2%.